Joseph Frank. Responses to Modernity: Essays in the Politics of Culture. New York: Fordham UP, 2012. x + 234 pp. - David W Foster (Studies in 20th & 21st Century Literature, 2014)
Review of Joseph Frank. Responses to Modernity: Essays in the Politics of Culture. New York: Fordham UP, 2012. x + 234 pp.
Keywords: literary theory; modern literature